Implementation of Smart Technology in Public Services in North Sulawesi - Ardiansyah, Ardiansyah (Asian Digital Governance Problems, 2024)
Purpose: This observe investigates the factors influencing perceptions and satisfaction with the implementation of smart era in public services in North Sulawesi. Subjects and Methods: Through a blended-approach approach, such as surveys and interviews, demographic variables which include age and years of service, as well as perceived effect, have been analyzed. Results: The findings screen that years of service extensively are expecting delight, highlighting the significance of organizational revel in in riding successful digital transformation tasks. Moreover, a strong correlation changed into found between perceived impact and pride, emphasizing the need for technological interventions to supply tangible benefits in public services. While age confirmed a vulnerable correlation with delight, similarly studies is wanted to discover the nuanced interaction among demographic factors and digital governance perceptions. Conclusions: Overall, this have a look at presents valuable insights for policymakers and practitioners seeking to layout effective digital governance strategies, emphasizing the significance of integrating technological answers with organizational lifestyle and stakeholder engagement.